Systematic review and meta-analysis of the effects of foot and ankle physical therapy, including mobilisations and exercises, in people with diabetic peripheral neuropathy on range of motion, peak plantar pressures and balance - Lepesis, V.; Marsden, J.; Rickard, A.; Latour, Jos; Paton, J. (2023)
To evaluate the effects of foot and ankle physical therapy on ankle and first metatarsophalangeal joint range of motion (ROM), peak plantar pressures (PPPs) and balance in people with diabetes. MEDLINE, EBSCO, Cochrane Database of Systematic Reviews, Joanna Briggs Institute Database of Systematic Reviews, PROSPERO, EThOS, Web of Science and Google Scholar were searched in April 2022. Randomised Controlled Trials (RCT), quasi-experimental, pre-post experimental design and prospective cohort studies were included. Participants were people with diabetes, neuropathy and joint stiffness. Interventions included physical therapy such as mobilisations, ROM exercises and stretches. Outcome measures focused on ROM, PPPs and balance. Methodological quality was assessed with Critical Appraisal Skills Programme RCT and Risk-of-Bias 2 tool. Meta-analyses used random-effects models and data was analysed using the inverse variance method. In total, 9 studies were included. Across all studies, participant characteristics were similar; however, type and exercise dosage varied greatly. Meta-analysis was performed with four studies. Meta-analysis showed significant effects of combined exercise interventions in increasing total ankle ROM (3 studies: MD, 1.76; 95% CI, 0.78–2.74; p = 0; I2 = 0%); and reducing PPPs in the forefoot area (3 studies; MD, −23.34; 95% CI, −59.80 to 13.13; p = 0.21, I2 = 51%). Combined exercise interventions can increase ROM in the ankle and reduce PPPs in the forefoot. Standardisation of exercise programmes with or without the addition of mobilisations in the foot and ankle joints needs further research.